Calidad de las instituciones de educación superior desde la perspectiva de América Latina y el Caribe (2021)
The quality of education entails the integral formation of citizens and, therefore, it is paramount for people and countries development. The education sector is bound to adequately respond with quality to the social and economic demands of Latin America and the Caribbean countries. This article aims at analyzing the concept of quality from the perspective of six countries in that region to identify how their quality assurance systems work and for establishing both similarities and differences. The case study and documentary analysis were used as information gathering techniques. The cases selecting criteria was to belong to the Ibero-American Network for Quality Assurance in Higher Education (RIACES) and to be positioned in the rankings. The results show that starting in the 1990s, quality improvement policies in the region's higher education institutions were further strengthened. It was concluded that, despite the progress made, there is still a great challenge in the regional integration of systems, the response to the context needs and the impact measurement.